TEACHERS’ PERCEPTIONS AND PRACTICES OF COMMUNICATIVE LANGUAGE TEACHING - Yanti, Gina Selvira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purposes of this research are to investigate teacher’s perceptions regarding their understanding on CLT principles, their perceived challenges in adapting CLT in their classrooms, and if there is a discrepancy between their perceptions toward CLT principles and their actual teaching practices. The context of this research was the English teachers in 44 different Junior High Schools in Mempawah district. This research is survey with descriptive quantitative in nature. The data was collected through a combination of questionnaires and classroom observation checklists. Based on the data which was gathered from the questionnaire and classroom observations, it was indicated that the teachers mostly had a good understanding about CLT principles. Unfortunately, they did not practice all of CLT principles in their teaching classroom. It was also found that most of the teachers deal with the perceived challenges. The major challenges they encounter were English skills proficiency, lack of training in CLT, a large size class and students’ low English proficiency. Keywords: Teachers’ perceptions, teaching practices, communicative language teaching. Abstrak: Tujuan penelitian ini adalah untuk menginvestigasi persepsi guru tentang pemahaman terhadap prinsip-prinsip CLT, tantangan yang mereka hadapi dalam mengaplikasikan CLT di kelas; dan apakah ada kesenjangan antara persepsi terhadap CLT dengan kegiatan mengajar mereka di dalam kelas. Penelitian ini dilaksanakan kepada guru mata pelajaran Bahasa Inggris di 44 SMP di Kabupaten Mempawah. Penelitian ini merupakan penelitian survey berbentuk kuantitatif kuantitatif. Data di kumpulkan dengan menggunakan kuesioner dan ceklis obervasi kelas. Berdasarkan data yang di peroleh dari kuesioner dan obervasi kelas, dapat disimpulkan bahwa hampir semua guru memahami prinsip-prinsip CLT dengan sangat baik. Namun, di dalam pelaksanaan mengajar mereka, tidak semua prinsip-prinsip CLT mereka terapkan. Berdasarkan data, dapat juga disimpulkan bahwa mereka berhadapan dengan tantangan-tantangan yang dirasakan. Tantangan terbesar yang mereka hadapi ialah minimnya kemampuan Bahasa Inggris mereka, kurangnya pelatihan tentang CLT, jumlah siswa yang besar, dan kemampuan Bahasa Inggris murid yang rendah. Kata kunci: Persepsi guru, praktik mengajar, pengajaran bahasa komunikatif